S132 Lineage tracing in humans reveals stochastic homeostasis of airway epithelium resulting from neutral competition of basal cell progenitors. (14th November 2013) - Teixeira, Vitor; Nadarajan, Parthiban; Graham, Trevor A; Pipinikas, Christodoulos P; Brown, James M; Falzon, Mary; Nye, Emma; Poulsom, Richard; Lawrence, David; Wright, Nicholas A; McDonald, Stuart; Giangreco, Adam; et al.
Abstract : In recent years, the development of lineage tracing approaches has provided quantitative new insights into tissue homeostasis in mice. However, the relevance of these discoveries to human epithelial homeostasis and alterations in disease is not known. We demonstrate that the statistical analysis of pathologically neutral somatic mitochondrial mutations that are accumulated over time can provide access to clonal fate behaviour at single cell resolution in human, providing a direct means to explore mechanisms of cell fate and tissue maintenance. Employing this approach, we define the progenitor cell population and the cellular hierarchy of the major human airways. By applying a novel quantitative approach to lineage tracing data, we conclude that, in normal homeostasis, the lining of human lung epithelium is maintained by an equipotent progenitor cell population of basal cells, in which the chance loss of cells due to commitment is perfectly compensated by the duplication of neighbouring cells, leading to neutral drift dynamics of the clone population. Further, we show that in airways of smokers, this process is accelerated leading to intensified clonal consolidation and a fertile background for tumorigenesis. This study provides the benchmark for the use of somatic mutations to quantitatively explore patterns of homeostatic growth in human tissues, and a platform to explore factors leading to homeostatic dysregulation and disease.